Reinventing the public square and early educational settings through culturally informed, community co-design: Playful Learning Landscapes - Pesch, Annelise; Ochoa, Karlena D.; Fletcher, Katelyn K.; Bermudez, Vanessa N.; Todaro, Rachael D.; Salazar, Julie; Gibbs, Hailey M.; Ahn, June; Bustamante, Andres S.; Hirsh-Pasek, Kathy (Frontiers in Psychology, 2022)
What if the environment could be transformed in culturally-responsive and inclusive ways to foster high-quality interactions and spark conversations that drive learning? In this paper, we describe a new initiative accomplishing this, called Playful Learning Landscapes (PLL). PLL is an evidence-based initiative that blends findings from the science of learning with community-based participatory research to transform physical public spaces and educational settings into playful learning hubs. Here, we describe our model for conducting this research, which is mindful of three key components: community input, how children learn best, and what children need to learn to be successful in a 21st-century economy. We describe how this model was implemented in two PLL case studies: one in a predominantly Latine community and the second in early childhood education classrooms. Furthermore, we describe how research employing our model can be rigorously and reliably evaluated using observational and methodological tools that respond to diverse cultural settings and learning outcomes. For example, our work evaluates how PLL impacts adult-child interaction quality and language use, attitudes about play and learning, and community civic engagement. Taken together, this paper highlights new ways to involve community voices in developmental and educational research and provides a model of how science can be translated into practice and evaluated in culturally-responsive ways. This synthesis of our process and evaluation methods can be used by researchers, policymakers, and educators to reimagine early educational experiences with an eye toward the built environment that children inhabit in everyday life, creating opportunities that foster lifelong learning.